Caracterização da prática dos terapeutas ocupacionais em cuidados paliativos nos serviços públicos oncológicos de saúde no Brasil - León Perilla, Viviana Marcela (2019)
Introduction: The occupational therapist (OT), by aiming to keep people with active participation in their daily lives, through the performance of activities that are significant to them, can compose the team of profissionals who work in oncological care and palliative care (PC). Oncological care, when combined with PC, produces better results than standard cancer treatment alone. Thus, it is essential to know deeply and systematize the performance of the OT in oncologic PC and its other constituent aspects. Objective: To understand how the insertion and performance of oncology in PC in hospital care is given to the oncologic population. Method: This is a quantitative-qualitative, exploratory study conducted in two stages: a) an online survey survey, and b) a multiple case study. For the first stage, an online questionnaire was used to collect data and, subsequently, a descriptive statistical analysis was carried out. In the second stage, different sources of evidence were used and triangulated (interviews, documentary consultation and electronic records) with subsequent cross-synthesis of the cases. Results: The first step was 18 OTs from three regions of Brazil (southeast, south and northeast), and in the second step, three OTs, randomly selected, one for each region. Sociodemographic characteristics, information about the work environment, the population attended and the profissional activities developed were identified. The findings of the 1st Stage showed greater insertion and consolidation of the practice of OT in PC in the Southeastern region, mean age between 25 and 45 years; predominance of the workload of 30 hours per week; in the outpatient care modality and in an advisory group of palliative care, in an interdisciplinary team. In addition, the prevalence of updating days, mostly involving action with adults and elderly with impaired functionality and physical symptoms, establishing objectives related to evaluation and therapeutic use of activities, preparation for the decline in health of the user at the end of life, emphasis on activities with meaning and significance in their day-to-day and recognition of the wishes of users for the establishment of therapeutic goals. In relation to the deepening obtained in the second stage, it was identified that the clinical/profissional reasoning is established to meet the physical, psychosocial, emotional and spiritual demands of the oncology population in PC, rescuing in its practice integrated actions to host the narratives, resignification of the life project, strengthening of bonds, as well as the optimization and maintenance of functional skills and occupational participation, and already to a lesser extent the facilitation of the process of leaving with the family. Within the obstacles, profissional training in the area was pointed out as insufficient specifically in the assessment, early attention and grief, and also in interdisciplinary work. Conclusion: it indicates the need to sensitize the interprofissional team about the potential of occupational therapy and its engagement in the creation of educational resources and profissional training in palliative care.